A kind of molybdenum tailings ceramsite and its preparation method and application

By mixing the merger and other materials in proportion to the ball, the molybdenum tail mine has been prepared to solve the problem of the waste and high energy consumption process of molybdenum tail mine resources, and the resource utilization and performance improvement is achieved.

CN116535118BActive Publication Date: 2025-01-28BEIJING DONGFANG JIANYU INST OF CONCRETE SCI & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310503113.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-06
Publication Date
2025-01-28
Estimated Expiration
2043-05-06

AI Technical Summary

Technical Problem

The accumulation of molybdenum tailings not only wastes resources and occupies land, but also causes pollution to the environment. The existing technology consumes a lot of energy and has poor economic and social benefits when preparing molybdenum tailings ceramic concrete.

Method used

The molybdenum mine powder, cement, air -induced water reducing agent, re -decentralized latex powder, cellulose, aluminum powder, and silicon powder are mixed in proportion to form and processes the process of ball Molybdenum tail mine ceramic grain.

Benefits of technology

The resource utilization of molybdenum tail ore is realized, the energy consumption of the preparation of molybdenum tailings is reduced, and the durability, freezing and permeability and wear resistance of pottery grains are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004214562140000041
    Figure BDA0004214562140000041
  • Figure BDA0004214562140000042
    Figure BDA0004214562140000042
  • Figure BDA0004214562140000071
    Figure BDA0004214562140000071
Patent Text Reader

Abstract

The present invention discloses a molybdenum tailings ceramsite and its preparation method and application, which are used to solve the resource utilization of molybdenum tailings and reduce the problem of high energy consumption in the process of preparing molybdenum tailings ceramsite concrete. A molybdenum tailings ceramsite comprises the following components by weight: 60-80 parts of molybdenum tailings powder, 10-20 parts of cement, 2-4 parts of air-entraining water-reducing agent, 5-10 parts of redispersible latex powder, 1-2 parts of cellulose, 2-5 parts of aluminum powder, 5-8 parts of silicon powder, and 10-20 parts of water. Molybdenum tailings powder is the main component to achieve resource utilization of molybdenum tailings. At the same time, molybdenum tailings powder is combined with cement to form ceramsite, without sintering, calcining, and steaming processes, which greatly reduces the energy consumption of preparing molybdenum tailings ceramsite. An application of molybdenum tailings ceramsite is also provided, which can be applied to the raw materials of lightweight concrete, and achieves resource utilization of molybdenum tailings while ensuring the strength of concrete.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of building materials, and in particular relates to molybdenum tailings ceramsite and a preparation method and application thereof. Background Art

[0002] With the rapid development of the national economy, the demand for molybdenum metal has gradually increased. Molybdenum metal has the characteristics of high conductivity, high strength, high melting point, and corrosion resistance, and is widely used in alloys, chemicals, electronics and other fields. The mining and processing volume of molybdenum ore in my country has also increased rapidly. Molybdenum tailings are the tailings left after the extraction of metallic molybdenum. my country is the world's largest molybdenum resource country, but due to the low molybdenum grade of molybdenum ore, in the process of extracting molybdenum resources with existing traditional technologies, more than 95% of the ore mining volume will be discharged as tailings. The accumulation of these molybdenum tailings not only wastes resources and occupies land, but also pollutes the surrounding environment. How to realize the resource utilization of molybdenum tailings is a technical problem that technicians in this field need to solve urgently.

[0003] The comprehensive utilization of molybdenum tailings mainly focuses on the extraction of valuable elements in molybdenum tailings and the preparation of new materials. In addition, molybdenum tailings contain some silicate minerals, so using molybdenum tailings powder as an admixture has become another important idea for the rational utilization of molybdenum tailings resources.

[0004] Domestic construction is moving towards industrialization, high-rise and large-span construction, which puts forward the requirements of lightweight and high-strength concrete. Ceramic aggregate concrete has the advantages of lightweight, high strength, thermal insulation, sound insulation, etc. While meeting the comfort of the residence, it can also effectively reduce the weight of the product, reduce the transportation and installation costs of the product, and improve the seismic performance of the structure. However, in the process of preparing molybdenum tailings ceramsite concrete, calcination, sintering and other processes are required, so the energy consumption is large, which is not in line with the sustainable development strategy, and the economic and social benefits are poor. Summary of the invention

[0005] The purpose of the present invention is to solve the resource utilization of molybdenum tailings and reduce the problem of high energy consumption in the process of preparing molybdenum tailings ceramsite concrete. A molybdenum tailings ceramsite and a preparation method and application thereof are provided.

[0006] In the first aspect, a molybdenum tailings ceramsite adopts the following technical solution:

[0007] A molybdenum tailings ceramsite comprises the following components in parts by weight: 60-80 parts of molybdenum tailings powder, 10-20 parts of cement, 2-4 parts of air-entraining water-reducing agent, 5-10 parts of redispersible latex powder, 1-2 parts of cellulose, 2-5 parts of aluminum powder, 5-8 parts of silicon powder and 10-20 parts of water.

[0008] By adopting the above technical solution, molybdenum tailings powder is used as the main component to realize the resource utilization of molybdenum tailings. At the same time, the molybdenum tailings powder is combined with cement to form expanded clay, which does not require sintering, calcining, and steaming processes, greatly reducing the energy consumption of preparing molybdenum tailings expanded clay.

[0009] Air-entraining water-reducing agent can be added to concrete to introduce tiny bubbles, improve the workability of concrete, reduce the bleeding and sedimentation of concrete, and improve the durability and corrosion resistance of molybdenum tailings ceramsite. At the same time, on the basis of improving the physical and mechanical properties of molybdenum tailings ceramsite, it can greatly improve the durability of concrete such as freeze-thaw resistance, frost resistance, and impermeability.

[0010] The addition of redispersible latex powder improves the tensile strength of the mixed mortar and thus enhances the impact toughness of the mixed mortar. In addition, it also gives the mixed mortar the stress field dispersion effect of the redispersible latex powder. The rubber powder has a certain water absorption, and together with the cellulose ether, it fully penetrates the surface of the base material, making the surface characteristics of the base and the new putty close, thereby improving the adsorption and greatly increasing its bonding properties. Reduce the ductility of the mixed mortar, improve the deformation ability of the redispersible latex powder, and reduce cracking. Improve the wear resistance of the mixed mortar.

[0011] The addition of cellulose can effectively prevent the shrinkage cracks of molybdenum tailings ceramsite, while significantly improving the mechanical properties of molybdenum tailings ceramsite and improving the durability of molybdenum tailings ceramsite.

[0012] Silica powder, as an auxiliary cementitious material, improves the microstructure of cement paste and has high volcanic ash activity. The silicon dioxide in silica powder is an acidic oxide, which hardens with medium-strong alkali calcium hydroxide and undergoes secondary hydration reaction to form hydrated calcium silicate gel, consuming calcium hydroxide and generating low-alkali hydrated calcium silicate with higher strength and better stability. This reaction optimizes the composition of the gel and improves its quality, which can significantly improve the product's compression, flexural, impermeability, corrosion, impact and wear resistance.

[0013] When a certain amount of aluminum powder is added, during the process of combining molybdenum tailings powder and cement to form ceramsite, aluminum powder reacts with the hydroxide ions produced during the hydration of cement to produce hydrogen, forming a large number of microbubbles, so that a porous structure is produced inside the prepared ceramsite product. The above components work synergistically to obtain molybdenum tailings ceramsite with low density and high strength, and at the same time can greatly reduce the water absorption performance of ceramsite.

[0014] Preferably, the molybdenum tailings powder has a specific surface area of ​​550-650m 2 / kg.

[0015] By adopting the above technical solution, the specific surface area of ​​the molybdenum tailings powder is controlled and the dispersibility of the molybdenum tailings powder in the mixture is enhanced.

[0016] Preferably, the air-entraining and water-reducing agent is one of lignin sulfonate, alkyl aromatic sulfonate, naphthalene sulfonate formaldehyde condensate, and polycarboxylate.

[0017] Preferably, the redispersible latex powder is one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer, and acrylic copolymer.

[0018] Preferably, the cellulose is one or more of methyl cellulose, ethyl cellulose and carboxymethyl cellulose.

[0019] In the second aspect, a method for preparing molybdenum tailings ceramsite adopts the following technical scheme:

[0020] A method for preparing molybdenum tailings ceramsite comprises the following steps:

[0021] Step 1), molybdenum tailings powder, cement, dispersible latex powder, cellulose, aluminum powder, silicon powder are weighed and mixed uniformly in proportion, water and air-entraining water-reducing agent are added in proportion and stirred evenly, and a sphere of 5-20 mm is formed through balling;

[0022] Step 2), the spheres obtained in step 1) are allowed to stand for 5-10 hours, and then covered with a film for heat preservation and moisture retention for 28 days to obtain molybdenum tailings ceramsite.

[0023] By adopting the above technical scheme, the components are mixed in proportion and formed into spheres through a ball-forming process. After standing, the molybdenum tailings expanded clay is obtained by coating and curing. This preparation method does not require calcination or sintering, and does not require a steaming process, thereby realizing the resource utilization of molybdenum tailings and significantly reducing energy consumption.

[0024] In the third aspect, an application of molybdenum tailings ceramsite adopts the following technical solution:

[0025] Any of the molybdenum tailings ceramsite described above can be applied to lightweight concrete.

[0026] By adopting the above technical solution, molybdenum tailings ceramsite is used as the raw material of lightweight concrete, which ensures the compressive strength of lightweight concrete while making resource utilization of molybdenum tailings. DETAILED DESCRIPTION

[0027] The present invention is described in further detail below in conjunction with the examples. For the sake of simplicity of description, this document cannot enumerate all the alternative technical features and implementation schemes included in the present invention, so those skilled in the art should know that any technical features and implementation schemes in the present embodiment do not limit the scope of protection of the present invention, and the scope of protection includes any alternative technical features and implementation schemes taken by all those skilled in the art without creative work. Specifically, the implementation schemes obtained by replacing any technical feature in the present invention or combining any two or more technical features provided by the present invention should be within the scope of protection of the present invention. Those who do not specify the specific techniques and conditions in the examples are carried out according to the techniques and conditions described in the literature in this field or according to the product instructions, and the reagents or instruments used are not indicated by the manufacturer, and are all conventional products that can be purchased commercially.

[0028] Molybdenum tailings powder: specific surface area 550-650m 2 / kg, specifically, the molybdenum tailings with a fineness modulus of 1.5 are dried and ground to prepare a powder with a specific surface area of ​​580 kg / m3 for standby use; the chemical composition mass percentages of the molybdenum tailings used in the following embodiments are shown in the following table:

[0029]

[0030] Cement: Cement with a grade of p.o42.5 or above can be used, and it is a commercially available product. The technical indicators of the cement used in the following embodiments are as follows:

[0031]

[0032] Silicon powder: silicon dioxide content of 90% or more; commercially available product. The chemical composition mass percentage of the silicon powder used in the following examples is shown in the following table:

[0033] project <![CDATA[SiO2]]> <![CDATA[Al2O3]]> <![CDATA[Fe2O3]]> CaO MgO IL Other Ingredients Silica Fume 94.58% 0.46% 0.15% 0.53% 0.37% 2.37% 1.54%

[0034] The air-entraining water-reducing agents are lignin sulfonates, alkyl aromatic sulfonates, and polycarboxylates, all of which are commercially available products.

[0035] Aluminum powder is a commercially available product. The aluminum powder used in the following embodiments can be selected to have a particle size of 80 mesh to 100 mesh.

[0036] Redispersible latex powder: polymer modified material, bridged in the product, as an elastic link between the components, making it flexible, and the modified network structure enables the product to resist impact without damage.

[0037] Example 1

[0038] A molybdenum tailings ceramsite provided in Example 1 includes the following components in parts by weight: 60 parts of molybdenum tailings powder, 10 parts of cement, 2 parts of air-entraining water-reducing agent, 5 parts of dispersible latex powder, 1 part of cellulose, 2 parts of aluminum powder, 5 parts of silicon powder, and 10 parts of water.

[0039] Among them, the specific surface area of ​​molybdenum tailings powder is 550m 2 / kg; the cement grade is 42.5; the air-entraining water-reducing agent is lignin sulfonate; the dispersible rubber powder is ethylene / vinyl acetate copolymer; and the cellulose is methyl cellulose.

[0040] The preparation method thereof comprises the following steps:

[0041] Step 1), first add the above proportions of molybdenum tailings powder, cement, redispersible latex powder, cellulose, aluminum powder, and silicon powder into a mixer and stir for 1 minute; add the above proportions of water and air-entraining water-reducing agent and stir for 1 minute; the mixture is balled into 10 mm ceramsite balls.

[0042] Step 2), after the ceramsite balls are formed, they are left to stand for 5 hours, and then covered with a film for heat preservation and moisture retention for 28 days before being shipped out of the factory.

[0043] Example 2

[0044] A molybdenum tailings ceramsite provided in Example 2 includes the following components in weight: 70 parts of molybdenum tailings powder, 15 parts of cement, 3 parts of air-entraining water-reducing agent, 8 parts of redispersible latex powder, 2 parts of cellulose, 4 parts of aluminum powder, 7 parts of silicon powder, and 15 parts of water.

[0045] Among them, the specific surface area of ​​molybdenum tailings powder is 600m 2 / kg; cement grade is 42.5; air entraining water reducer is alkyl aromatic sulfonate, dispersible latex powder is vinyl acetate / versatate copolymer; cellulose is ethyl cellulose;

[0046] The preparation method thereof comprises the following steps:

[0047] Step 1), first add the above proportions of molybdenum tailings powder, cement, redispersible latex powder, cellulose, aluminum powder, and silicon powder into a mixer and stir for 1 minute; add the above proportions of water and air-entraining water-reducing agent and stir for 1 minute; the mixture is balled into 10 mm ceramsite balls.

[0048] Step 2), after the ceramsite balls are formed, they are left to stand for 8 hours, and then covered with a film for heat preservation and moisture retention for 28 days before being shipped out of the factory.

[0049] Example 3

[0050] A molybdenum tailings ceramsite provided in Example 2 includes the following components in parts by weight: 80 parts of molybdenum tailings powder, 20 parts of cement, 4 parts of air-entraining and water-reducing agent, 10 parts of redispersible latex powder, 2 parts of cellulose, 5 parts of aluminum powder, 8 parts of silicon powder, and 20 parts of water.

[0051] Among them, the specific surface area of ​​molybdenum tailings powder is 650m 2 / kg; the cement grade is 42.5; the air-entraining water-reducing agent is naphthalenesulfonate formaldehyde condensate; the redispersible latex powder is acrylic acid copolymer; and the cellulose is ethyl cellulose.

[0052] The preparation method thereof comprises the following steps:

[0053] Step 1), first add the above proportions of molybdenum tailings powder, cement, redispersible latex powder, cellulose, aluminum powder, and silicon powder into a mixer and stir for 1 minute; add the above proportions of water and air-entraining water-reducing agent and stir for 1 minute; the mixture is balled into 10 mm ceramsite balls.

[0054] Step 2), after the ceramsite balls are formed, they are left to stand for 10 hours, and then covered with a film for heat preservation and moisture retention for 28 days before leaving the factory.

[0055] In the molybdenum tailings ceramsite provided in Example 4-5, the cement grade is 42.5; the air-entraining water-reducing agent is a naphthalenesulfonate formaldehyde condensate; the redispersible latex powder is an acrylic acid copolymer; and the cellulose is ethyl cellulose.

[0056] Example 4

[0057] A molybdenum tailings ceramsite provided in Example 4 includes the following components in weight: 75 parts of molybdenum tailings powder, 10 parts of cement, 2 parts of air-entraining water-reducing agent, 5 parts of redispersible latex powder, 1 part of cellulose, 3 parts of aluminum powder, 6 parts of silicon powder, and 15 parts of water.

[0058] The preparation method thereof comprises the following steps:

[0059] Step 1), first add the above proportions of molybdenum tailings powder, cement, redispersible latex powder, cellulose, aluminum powder, and silicon powder into a mixer and stir for 1 minute; add the above proportions of water and air-entraining water-reducing agent and stir for 1 minute; the mixture is balled into 10 mm ceramsite balls.

[0060] Step 2), after the ceramsite balls are formed, they are left to stand for 5 hours, and then covered with a film for heat preservation and moisture retention for 28 days before being shipped out of the factory.

[0061] Example 5

[0062] The difference between the molybdenum tailings ceramsite provided in Example 5 and Example 4 is that the molybdenum tailings ceramsite provided in Example 5 includes the following components in weight: 67 parts of molybdenum tailings powder, 15 parts of cement, 3 parts of air-entraining water-reducing agent, 6 parts of redispersible latex powder, 1 part of cellulose, 3 parts of aluminum powder, 8 parts of silicon powder, and 15 parts of water.

[0063] Comparative Example

[0064] The molybdenum tailings ceramsite provided in Comparative Examples 1-4 is different from that in Example 5 in that the components of the molybdenum tailings ceramsite in Comparative Examples 1-4 are shown in Table 1 below.

[0065] Table 1

[0066]

[0067] Comparative Example 1

[0068] The molybdenum tailings ceramsite provided in Comparative Example 1 is different from that in Example 5 in that the redispersible latex powder in Comparative Example 1 is replaced by cellulose in equal amounts.

[0069] Comparative Example 2

[0070] The molybdenum tailings ceramsite provided in Comparative Example 2 is different from that in Example 5 in that an equal amount of cellulose in Comparative Example 2 is replaced by redispersible latex powder.

[0071] Comparative Example 3

[0072] The molybdenum tailings ceramsite provided in Comparative Example 3 is different from that in Example 5 in that an equal amount of aluminum powder is replaced by molybdenum tailings powder in Comparative Example 3.

[0073] Comparative Example 4

[0074] The molybdenum tailings ceramsite provided in Comparative Example 4 is different from that in Example 5 in that an equal amount of silicon powder is replaced by molybdenum tailings powder in Comparative Example 4.

[0075] Application Examples

[0076] Application Example 1

[0077] Application Example 1: The molybdenum tailings ceramsite provided in Example 4 is applied to the components of C10, C20, and C30 strength grade concrete.

[0078] Application Example 2

[0079] Application Example 2: The molybdenum tailings ceramsite provided in Example 5 is applied to the components of C10, C20, and C30 strength grade concrete.

[0080] Performance Testing

[0081] The bulk density, cylinder pressure strength, 1h water absorption, softening coefficient, ignition loss and mud content of the molybdenum tailings ceramsite provided in Examples 1-5 and Comparative Examples 1-4 were tested for performance, as shown in Table 2. The concrete components of different strength grades provided in Application Example 1 are shown in Table 3, and the concrete components of different strength grades provided in Application Example 2 are shown in Table 4.

[0082] Table 2

[0083] project <![CDATA[Bulk density kg / m 3 > Cylinder pressure strength MPa 1h water absorption % Softening coefficient Loss on ignition% Example 1 1000 3.6 7.9 0.95 2.39 Example 2 1000 4.0 8.5 0.94 2.42 Example 3 1100 3.8 8.1 0.88 2.48 Example 4 1000 3.9 8.3 0.92 2.43 Example 5 1100 4.3 7.5 0.96 2.40 Comparative Example 1 1300 3.5 8.8 0.85 2.43 Comparative Example 2 900 3.2 11.2 0.72 2.41 Comparative Example 3 1200 3.0 9.6 0.80 2.45 Comparative Example 4 1100 3.4 10.5 0.69 2.36

[0084] Table 3

[0085]

[0086] Table 4

[0087]

[0088] For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived from them are still within the scope of protection of the claims of the invention.

Claims

1. A molybdenum tailings ceramsite, characterized in that: The invention comprises the following components in parts by weight: 60-80 parts of molybdenum tailings powder, 10-20 parts of cement, 2-4 parts of air-entraining water-reducing agent, 5-10 parts of redispersible latex powder, 1-2 parts of cellulose, 2-5 parts of aluminum powder, 5-8 parts of silicon powder and 10-20 parts of water; The cellulose is one or more of methyl cellulose, ethyl cellulose and carboxymethyl cellulose; The preparation method of the molybdenum tailings ceramsite comprises the following steps: Step 1), molybdenum tailings powder, cement, redispersible latex powder, cellulose, aluminum powder, silicon powder are weighed and mixed uniformly in proportion, water and air-entraining water-reducing agent are added in proportion and stirred evenly, and a sphere of 5-25 mm is formed through balling; Step 2), the spheres obtained in step 1) are allowed to stand for 5-10 hours, and then covered with a film for heat preservation and moisture retention for 28 days to obtain molybdenum tailings ceramsite.

2. A molybdenum tailings ceramsite according to claim 1, characterized in that: The molybdenum tailings powder has a specific surface area of ​​550-650m 2 / kg.

3. A molybdenum tailings ceramsite according to claim 1, characterized in that, The air-entraining water-reducing agent is one of lignin sulfonate, alkyl aromatic sulfonate and polycarboxylate.

4. A molybdenum tailings ceramsite according to claim 1, characterized in that, The dispersible latex powder is one of ethylene / vinyl acetate copolymer, vinyl acetate / versatate copolymer and acrylic acid copolymer.

5. An application of molybdenum tailings ceramsite, characterized in that: The molybdenum tailings ceramsite as described in any one of claims 1 to 4 can be applied to lightweight concrete.

Citation Information

Patent Citations

  • Method for preparing ceramsites and ceramsites prepared by method

    CN106587765A

  • Molybdenum tailing ceramsite and preparation method thereof

    CN112624645A